Low cycle fatigue behavior of precipitation-strengthened Cu-Cr-Zr contact wires. (August 2020) - Wang, Junfeng; Chen, Jinshui; Guo, Chengjun; Xiao, Xiangpeng; Wang, Hang; Yang, Bin
Highlights: The LCF behavior of Cu-Cr-Zr alloy at room temperature has been depth studied. The fatigue fracture surface at different Δεt /2 showed a great difference. The original characteristics were increasingly less with the rises of Δεt /2. The dislocation density after different Δεt /2 was calculated exactly by XRD. Abstract: The low cycle fatigue behavior (Δεt /2 = 0.4–1.0%) of a Cu-Cr-Zr alloy strengthened with nanoscale precipitates has been tested at room temperature. The results showed that cyclic softening occurs under all Δεt /2 after cyclic hardening. However, the Cu-Cr-Zr alloy exhibited secondary cycle hardening after a brief softening at high Δεt /2 (0.8%, 1.0%). In strong contrast to the fatigue fracture surface at Δεt /2 = 0.4%, Δεt /2 = 1.0% was characterized by multiple fatigue sources and obvious fatigue striations. Moreover, a sawtooth-like feature formed and the fracture mode was mainly brittle with few regions of ductile aspects. Compared with the original characteristics, the microstructure after different values of Δεt /2 was markedly different, and the dislocation density gradually increased with the increases of Δεt /2.